(untitled) (Research, Society and Development, 2025)
Cytology is the branch of Biology dedicated to the study of cells. The existing difficulties in understanding the contents of this area are notorious. This process can be facilitated with the use of didactic resources, such as models, as they allow a better visualization of the studied structures and make the content more tangible. From this, the present work aimed to compare how high school students learn about cellular organelle content based on the use and non-use of models. The research took place with a qualitative approach, with the participation of two third grade high school classes, in a public state school in the municipality of São Francisco do Piauí/PI. It was verified that the use of the model provided a greater understanding of the cellular organelles content, in addition to being efficient for the motivation of the students, which can make the classes more dynamic and stimulating. With this, one can see the importance of using this didactic resource in the teaching and learning process.